Co-producing just and sustainable localities: emphasising the role of local authorities in current practices in Germany - Weck, Sabine; Ritzinger, Anne (DIE ERDE – Journal of the Geographical Society of Berlin, 2021)
In current debates on socio-ecological transformation, a growing number of stakeholders are highlighting the need to consistently move away from growth pressures. Several urban and rural development initiatives are pioneering alternative local production and consumption patterns in sustainable and integrated land use. Taking a spatial perspective, we discuss promising initiatives in three fields which we see as paradigmatic for a new kind of co-produced local development geared to a fairer and more sustainable future: co-operation projects between municipalities and community enterprises, participatory approaches to sustainable land use in rural communities, and collaborative development for sustainable urban residential estates. The aim of the paper is to discuss the transformative potential of these paradigmatic initiatives and what should be done to serve their interests and promote their mainstreaming. We draw on a diverse economies framing (Gibson-Graham 2008), arguing that it is important to bring these nascent post-growth practices to the attention of academic practice as well as politicians. Understanding these newly emerging practices in their potential and constraints is key to ultimately stimulating broader societal trend towards more just and sustainable localities. We argue that German municipalities have a fair amount of leeway in shaping the interplay of stakeholders and the interface between bottom-up initiatives and top-down steering policies towards just and sustainable localities. Our analysis emphasises the agency of local municipalities and their discretionary power to initiate change and transformation.